FORMATION OF CONNOTATIVE MEANING THROUGH ARTISTIC AND VISUAL MEANS - Mo'minova Yulduz Aminboyevna; Reyimboyeva Muyassar Azimboyovna (Western European Studies, 2024)
The emotional expressiveness of the language units used in the work of art is considered to be the main task of performing a methodological task. This thing gives rise to the specific semantic-stylistic features of the artistic visual tools in the text of the artistic work and the state of impact of the work. The means of artistic images are more beautiful and effective in poetry
Keywords: poetry; language units; animation